KEPUASAN PASIEN RUMAH SAKIT DIUKUR DARI KUALITAS PELAYANAN DAN CITRA RUMAH SAKIT - ANITA SUMELVIA DEWI; DIANA AMBARWATI (Jurnal Akademika, 2022)
This study analyzed the effect of service quality and image on patient satisfaction at Arga Husada Hospital, Kediri. The formulation of the problem in this study is the extent to which the influence of service quality and image has an effect on patient satisfaction at the Arga Husada Hospital, KediriThe sampling technique in this study used the non-probability sampling method and the number was 113 respondents. Data obtained through questionnaires. The analysis technique used in this study is the classical assumption test and using multiple linear regression for hypothesis testing. The results of this study indicate that simultaneously service quality and image have a significant effect on patient satisfaction at Arga Husada Hospital, Kediri. Partial test shows that service quality and image have a significant effect on patient satisfaction at Arga Husada Hospital, KediriKeywords: service quality, image, patient satisfaction